Single Treatment, Single Depth Superficial Microfocused Ultrasound with Visualization for Rhytid Improvement. Issue 7 (13th July 2021) - Lowe, Stephen
Abstract : Background: Standard lifting and tightening protocols with microfocused ultrasound with visualization (MFU-V, Ultherapy) comprise the use of multiple transducer depths. We developed a shortened, single depth treatment protocol for patients seeking skin rejuvenation. Methods: Single-center, prospective case series. Subjects with static periorbital wrinkles, perioral wrinkles, or accordion lines had a single MFU-V treatment comprising up to 340 lines (periorbital 120, perioral 100, and accordion 120) with the superficial depth transducer (10.0 MHz/1.5 mm). Efficacy was assessed using established rating scales as well as clinician- and subject-reported Global Aesthetic Improvement Scales at baseline, 90, and 180 days, and each subject served as their own control. Adverse events were documented. Results: Nine subjects, women aged 38–64, received treatment. At 180 days, post treatment clinicians reported visible improvements in periorbital lines (6/6 cases), accordion lines (5/6 cases), and perioral lines (3/6 cases). Subjects' self-assessments mirrored those of the clinicians, reporting improvements in accordion lines (5/6 cases improved, 1/6 cases much improved), periorbital lines (3/6 cases improved, 3/6 cases much improved) and perioral lines (2/6 cases improved, 2/6 cases much improved). Subject-rated satisfaction was high (accordion lines 6/6 cases, periorbital lines 4/6 cases and perioral lines 4/6 cases). All subjects experienced mild, transient erythema; in one subject, wheals persisted for 24 hours, resolving on application of mild topical corticosteroid. Conclusions: Shortened protocol, single depth MFU-V treatment was well-tolerated. It provided aesthetic improvements in periorbital and accordion lines, and to a lesser extent in perioral lines. Its utility as a noninvasive therapy for superficial skin rejuvenation warrants further investigation.